Is Mail Service Pharmacy Cost Beneficial to Plan Sponsors? - Larisa Vulakh, Student Pharmacist; Albert I. Wertheimer, PhD, MBA (University of Minnesota Libraries Publishing, 2011)
The objective of this study was to describe and compare prescription drug costs charged to a plan sponsor for the top 50 maintenance medications provided through retail and mail service procurement channels. Data were obtained for covered beneficiaries of a health plan sponsored by an employer with just over 3,000 covered employees The analytics team at the PBM administering the plan sponsor's prescription drug benefit provided de-identified claims information for the top 50 maintenance prescription drugs delivered through either mail service or retail procurement methods for this employer over a one year period (7/1/2008 to 6/30/2009). Based on these data, (1) dollar amount difference (mail service minus retail), and (2) percentage difference between mail and retail costs (as a percentage of the lower net cost per day) were computed. The findings revealed that 76 percent of the medication products studied were associated with a lower net cost per day to the plan sponsor through mail service procurement and 24 percent were associated with lower net cost through retail procurement.